A method of constructing and using the tree of possible transformations from UNL to the natural language - Levon R. Hakobyan (АН Арм. ССР)
An approach to improving the transformation process from UNL to natural language is described. We introduce the tree of possible transformations, which lets us generate all the possible transformation paths for the current sentence and rule set. The implementation of the algorithm in UNDL Platform is described.
Keywords: Mathematics; Computer software